Freshman sailing team - Unknown (Tufts Archival Research Center, 2014)
photographic print. Group picture of the Tufts freshman sailing team, spring 1972 First row (L-R): Dave Winkler, Alan Howell (captain), Andy Hawks, Dave Archibald Second row: Joe Duplin (coach), Peter Wells, Dave barrett, Andy Shepard, Bill Garfield (assistant coach)